A revision of Sunius XV. Six new species from Kyrgyzstan and the Himalaya, and additional records (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2015)
Six micropterous species of Sunius Stephens, 1829 are described and illustrated: S. alaianus spec. nov. (Kyrgyzstan) of the S. viator group; S. marratus spec. nov. (North India: West Bengal), S. virilis (North India: West Bengal), S. deplectens spec. nov. (North India: West Bengal), S. dearmatus spec. nov. (East Nepal), and S. migrus spec. nov. (Central Nepal), all five of them of the S. manasluensis group. Additional records of 16 species are reported both from the West and the East Palaearctic regions. The genus is now represented in the Palaearctic region by 126 described species and two subspecies. Keywords Coleoptera, Staphylinidae, Paederinae, Medonina, Sunius, Palaearctic region, Kyrgyzstan, Himalaya, taxonomy, new species, new records, species groups. Nomenclatural Acts alaianus Assing, 2015 (Sunius), spec. n. dearmatus Assing, 2015 (Sunius), spec. n. deplectens Assing, 2015 (Sunius), spec. n. marratus Assing, 2015 (Sunius), spec. n. migrus Assing, 2015 (Sunius), spec. n. virilis Assing, 2015 (Sunius), spec. n.